Association of Astigmatism with Allergic Conjunctivitis - Naseer, Muhammad Saad; Parveen, Shagufta; Muhammad Jahanzaib; Ahmad Khan, Fawad; Sajjad, Sania; Zahra, Syeda Muniba (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the association of astigmatism with allergic conjunctivitis. Study Design: Prospective observational study. Place and Duration of Study: Armed Forces Institute of Ophthalmology, Jun to Dec 2023. Methodology: The study had 359 patients, and convenience sampling was performed. Baseline data was collected related to demographic characteristics, past medical history and co-morbidities. Allergic Conjunctivitis was diagnosed through examination with a slit-lamp. Astigmatism was diagnosed by measuring the refractive power of both eyes using an Automated Kerato Refractometer. Patients were pre-evaluated for Astigmatism and they were followed for period of 6 month. And post evaluated after 3 weeks, 3 months and 6 months. Data was collected, entered and analyzed in SPSS version 26.0. Chi Square test was applied and p<0.05 was considered as significant. Results: Out of 359 patients, 176(49.02%) were male and 183(50.98%) were females. Patients were pre-evaluated at baseline for astigmatism and none reported condition. At baseline (week 1) 27(7.53%) of them had the disease. At the 6th month follow-up, astigmatism in patients rose to 202(56.26%) respectively. The data analysis showed a significant association of Astigmatism with allergic conjunctivitis at the 6th-month follow-up (p value < 0.001). Conclusion: Astigmatism is significantly associated with allergic conjunctivitis.